Parcularity of the geoid determination at the Antarctic region - Marchenko, D. O.; Maksymchuk, V. U. (Ukrainian Antarctic Journal, 2012)
The gravitation effect of topographic masses is very important for the gravity anomaly calculations and geoid heights determination. The new approach for the computation of the topographic-isostatic corrections and indirect effect of topography in spherical approximation is developed and tested in Antarctic region.